Analysis of the Effect of Food Prices, GDP, Inflation, and Exchange Rate on Poverty in 4 ASEAN Countries - Prayoga, Akbar Eka; Nazamuddin, B.S; Dawood, Taufiq C. (PT. Hafasy Dwi Nawasena, 2025)
Poverty remains a persistent challenge in ASEAN countries despite economic growth. A 2024 World Bank report highlights that many families, especially in agriculture-dependent economies, still live below the poverty line. This study examines the impact of food prices, GDP, inflation, and exchange rates on extreme poverty in Indonesia, Malaysia, Thailand, and the Philippines from 1991 to 2021, using data from the World Bank and FAOstat. The analysis employs a pooled panel ARDL model with diagnostic tests (Wald, residual normality, and CUSUM) and robustness checks (Hausman Test and OLS). Findings indicate that, in the long run, extreme poverty is negatively and significantly influenced by food prices and exchange rates. Rising food prices increase income for farmers, improving rural livelihoods, but they also reduce the purchasing power of net consumers. Exchange rate depreciation raises import costs, affecting affordability of essentials. GDP and inflation show an insignificant effect on extreme poverty in the long run. In the short run, the exchange rate has a positive significant effect on extreme poverty, while the other variables remain insignificant. Currency depreciation boosts agricultural exports, employment, and local industries. This study recommends policies to stabilize food prices and address currency depreciation, while fostering inclusive growth and mitigating inflationary pressures to reduce extreme poverty in ASEAN nations.